The Capital and Labor Elasticities of Aggregate Output - Ali Motavasseli (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2022)
The elasticity of aggregate output with respect to aggregate capital and labor is computed using the cost structure of the production network of Iran's economy without using the aggregate production function. Estimations are made using Input-Output tables and according to a method developed by Baqaee and Farhi (2019, 2020). Elasticities are computed for the years 1986, 1999, 2001, 2004, 2010, 2011, and 2016. Various assumptions regarding capital costs of production sectors lead to lower and upper bounds for capital elasticity. The bounds for capital elasticity of Iran's economy were 0.15-0.35 in 1986, up to 0.22-0.55 in 1999, 2001, and 2004, even higher to 0.28-0.59 in 2010 and 2011, and down to 0.21-0.42 in 2016. Labor elasticities are one minus capital elasticities. Notably, the bounds for capital elasticity steadily increased from 1986 until the early 2010s, followed by a decline. For the non-oil sectors, the bounds for capital elasticity and the spread between those bounds are smaller than the entire economy. The bounds for the non-oil economy are 0.15-0.32 in 1986, up to 0.17-0.47 from 1999 to 2011, and 0.17-0.35 in 2016. The results show that ignoring labor compensation from unincorporated sectors of the economy increases the capital elasticity by at least 0.17 points. Our estimations can be used for robustness check and sensitivity analysis wherever capital and labor elasticities are needed, such as growth accounting.